Morphology of the Io Plasma Torus From Juno Radio Occultations. Issue 10 (5th October 2021) - Moirano, A.; Gomez Casajus, L.; Zannoni, M.; Durante, D.; Tortora, P.
Abstract: The jovian moon Io disperses about 1 ton/s of material in the planetary magnetosphere, mainly by sublimation of SO2 from the surface and by its intense volcanic activity. The ejected material supplies the plasma cloud surrounding Jupiter known as Io Plasma Torus (IPT). The radio communication between Juno and the Earth DSN station crosses the IPT near the closest approach. Being a dispersive medium, the IPT introduces a path delay in the signal, which can be analyzed to retrieve the density distribution of electrons. We used radio tracking data from the first 25 orbits to investigate the morphology of the IPT and its variability. We adopted a static and axisymmetric model for the electron density and we updated it including temporal and longitudinal variability. We found that our best fit model must include both variabilities, even though on average the morphology of the IPT agrees with previous analyses. Our results suggest that the density of the outer region of the IPT fluctuates over 50% the average value over a typical time scale of about 420 days. Key Points: Density distribution of electrons in the Io plasma torus is derived from the first 15 radio occultations by Juno Temporal and longitudinal variabilities in the electron density of the torus are presented Density in the Io torus fluctuates over about 50% the average value and the typical time scale of periodic variation is about 430 days